PRMT5 Inhibition Promotes PD-L1 Expression and Immuno-Resistance in Lung Cancer - Hu, Rui; Zhou, Bingqian; Chen, Zheyi; Chen, Shiyu; Chen, Ningdai; Shen, Lisong; Xiao, Haibo; Zheng, Yingxia (Frontiers in Immunology, 2022)
Protein arginine transferase 5 (PRMT5) has been implicated as an important modulator of tumorigenesis as it promotes tumor cell proliferation, invasion, and metastasis. Studies have largely focused on PRMT5 regulating intrinsic changes in tumors; however, the effects of PRMT5 on the tumor microenvironment and particularly immune cells are largely unknown. Here we found that targeting PRMT5 by genetic or pharmacological inhibition reduced lung tumor progression in immunocompromised mice; however, the effects were weakened in immunocompetent mice. PRMT5 inhibition not only decreased tumor cell survival but also increased the tumor cell expression of CD274 in vitro and in vivo, which activated the PD1/PD-L1 axis and eliminated CD8+T cell antitumor immunity. Mechanistically, PRMT5 regulated CD274 gene expression through symmetric dimethylation of histone H4R3, increased deposition of H3R4me2s on CD274 promoter loci, and inhibition of CD274 gene expression. Targeting PRMT5 reduced this inhibitory effect and promoted CD274 expression in lung cancer. However, PRMT5 inhibitors represent a double-edged sword as they may selectively kill cancer cells but may also disrupt the antitumor immune response. The combination of PRMT5 inhibition and ani-PD-L1 therapy resulted in an increase in the number and enhanced the function of tumor-infiltrating T cells. Our findings address an unmet clinical need in which combining PRMT5 inhibition with anti-PD-L1 therapy could be a promising strategy for lung cancer treatment.